(untitled) (Italian Journal of Public Health, 2004)
Background. Various projects have identified the need for common indicators for comparing countries and more recently, regions. The Vienna publication aims to contribute to this discussion. Methods and Results. While not perfect, aggregate measures such as life expectancy and mortality can act as indicators of the general level of health in international comparisons. They are relatively reliable and easily accessible and are often available at regional levels. Conclusion. Despite their limitations, international reference values provide relevant information on the position of a country or city within Europe. They can provide inspiration and motivation for policy makers and visualise past successes